n‐Type GaSe Thin Flake for Field Effect Transistor, Photodetector, and Optoelectronic Memory - Kumar, Arun; Pelella, Aniello; Intonti, Kimberly; Viscardi, Loredana; Durante, Ofelia; Giubileo, Filippo; Romano, Paola; Neill, Hazel; Patil, Vilas; Ansari, Lida; Hurley, Paul K.; Gity, Farzan; et al. (Advanced electronic materials, 2024)
The family of 2D chalcogenide semiconductors has been growing rapidly. Metal monochalcogenides, for instance, can enable new possibilities in functional electronics and optoelectronics. A Gallium Selenide (GaSe) thin flake is used to fabricate a back gated field effect transistor (FET) with n‐type conduction behavior and wide hysteresis at the ambient conditions. The device shows high mobility up to 28 cm2 V−1 s−1 with Ion/Ioff ratio over 103. Under the laser exposure, the device shows a decrease in the threshold voltage and a left‐shift of the transfer characteristic with a slight increase in the current. The transfer characteristic exhibits a hysteretic behavior with hysteresis width linearly dependent on the applied gate voltage. Moreover, the GaSe‐based FET shows a photo response with a photoresponsivity of 475 mAW−1 and detectivity of 4.6 × 1012 Jones. The photocurrent rise and decay times are 0.1 and 1.3 s, respectively. Furthermore, the GaSe FET device can be used as a performant memory device with well separated states and memory window enhanced by the laser exposure, confirming an optoelectronic memory class. Gallium–Selenide (GaSe) thin‐flake shows n‐type conduction in a field‐effect transistor with Ni contacts. The transfer characteristic exhibits a hysteretic behavior and high photo response, which are exploited to demonstrate an optoelectronic memory device.